PENGENDALIAN HARGA PADA PROGRAM TOKO TANI INDONESIA CENTER PROVINSI SUMSEL DALAM PERSPEKTIF EKONOMI ISLAM - Amrillah Amrillah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2020)
Rice, Market, Price and government intervention are a unified whole that cannot be separated. If the market is not stable it will affect the price. This paper aims to describe and explain why controlling rice prices needs to be done by the government through the TTIC program in South Sumatra from the perspective of an Islamic economic perspective. study of the perspective of Islamic economics that recognizes free markets. Prices are submitted to the market where prices are formed at the request and supply so that a normal price is formed. The government is not allowed to intervene when prices are normal. The government is only justified in an emergency by promoting the concept of justice. The al-Hisbah institution functions as an independent institution that is free from the interests of certain groups. The intervention of the price of rice by the government aims to benefit the masses so that it does not overburden the community when the price of rice surges. This government program is carried out to keep prices stable when market demand increases. This type of research is field research conducted using a qualitative approach, this study departs from the conditions in the field in order to see and understand the phenomena that exist and are reversed in more depth. Symptoms include the views, thoughts, attitudes and actions of the informants, and also include the situations and conditions observed as well as the data which are the Sumatran TTI Center documents. The results of this study indicate that the government has carried out its role as a state institution that functions to control prices when prices rise in the community.